Alat Deteksi Denyut Jantung Tipe Fingertip dengan Sensor Non-invasif untuk Masyarakat Pedesaan (Studi Kasus Desa Raharja, Banjar, Jawa Barat) - Maria Evita; Prihatini, Jihan; Sawita, I Kadek Agus Sara; Kamal, Muhammad; Aprianti, Nur Asiah (Jurnal Fisika Unand, 2025)
Heart disease is one of the most lethal diseases in the world, including in Indonesia. This disease affects both urban and rural populations Lack of access to medical equipment particularly for heart rate detection, is the reason for developing a fingertip-type heart rate device using a cheap and convenient non-invasive sensor. This system consists of an infrared sensor equipped with an analog filter, an operational amplifier and Arduino Uno microcontroller for signal processing, and an LCD for displaying the heart rate. After calibration, this system was tested on 20 participants in Desa Raharja to validate its performance. In two phases of testing, the average accuracy obtained ranged from 3.28% to 8.08% in phase 1, and from 2.89% to 31.73% in phase 2. Most of the results have met the accuracy standards for heart rate detection equipment. The shortcomings of this research allow for further development in future studies.